Students' Creative Thinking Process in Solving Multiple Solution Tasks on Geometry Material - Pradiarti, Refni Adesia; Sudirman, Sudirman; Sisworo, Sisworo (Jurnal Pendidikan MIPA, 2024)
This research is a qualitative descriptive research which aims to explore students' creative thinking process in completing MST on geometry material. The creative thinking process of each individual is different according to their level so it is necessary to analyze how students' creative thinking process is in completing MST based on level of creative thinking. Researchers refer to the stages of creative thinking developed by Wallas consisting of preparation, incubation, illumination and verification stages. Researchers focused subjects on the 5 levels of creative thinking developed by Siswono in the stages of creative thinking, namely subjects with levels of creative thinking level 4 (very creative), 3 (creative), 2 (quite creative), 1 (less creative), and 0 (not creative). Each level is described starting from the preparation, incubation, illumination and verification stages. Based on the research results, there are differences in creative thinking processes at each level of creative thinking, especially at the verification stage, only students with creative levels 4, 3, and 2 carry out the verification stage; The incubation stage for students with creative levels 2, 1, and 0 takes a long time so that subjects with a long incubation stage are not optimal in completing MST to get many alternative solutions.      Keywords: geometry, multiple solution tasks, creative thinking process.DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp248-263